Evaluating the performance of rural areas in improving entrepreneurship infrastructure for the development of rural entrepreneurship in Khalilabad city - Akherati Ivari, Ayoub (2021)
Entrepreneurship in order to generate income and employment is one of the most important tools for rural development and the present study has been prepared with the same purpose and as the evaluation of rural performance in improving entrepreneurship infrastructure for rural entrepreneurship development in Khalilabad city. The present research is applied in terms of purpose and in terms of descriptive-analytical method, which used library and field methods to collect information and a researcher-made questionnaire for field data. The sample population was randomly studied using Cochran's formula including 370 people in 23 villages of the city. The results obtained in the villages of the city show that the performance of rural villagers in Khalilabad city in order to develop rural entrepreneurship has been weak. The villages of the city, except for the development of public infrastructure (water, electricity, etc.) in other areas of entrepreneurial infrastructure have not performed well and have not been able to achieve the desired goals.